Potential of Ecoenzymes and N2 Nanobubbles on the Growth of Phalaenopsis sp. Orchid at the Acclimatization Stage - Syafitri, Fitria Indah; Rahayu, Tintrim; Jayanti, Gatra Ervi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2024)
Growth is a quantitative change during one plant’s life cycle and is irreversible.withaddition An in crease the volume or dry weight of plants or other organs is due to the adding, of new structural elements. Phalaenopsis (moth orchid) is a genus of orchids appeal. The diversity of colors, shapes, and textures, as well as its aroma, make Phalaenopsis orchids one of the charming flowers of Indonesia. Ecoenzyme is a solution of complex organic substances produced from the fermentation of organic residues, sugar, and water. Nanobubbles (NBs) are an example of nanotechnology. NBs have a diameter of 1-100 nm and are nanoscopic gas bubbles in a solution or water that can change the characteristics of water and are stable. This study aims to determine the potential of giving Ecoenzyme and NBs N2 on the growth of Phalaenopsis orchids during the acclimatization stage. This research was conducted from October to December 2022 at the Orchidology and Nursery Laboratory, Islamic University of Malang. This study used an experimental method with a completely randomized design (CRD) with 10 treatments, namely 0 mL/L (control), 1 mL/L Ecoenzyme, 2 mL/L Ecoenzyme, 3 mL/L Ecoenzyme, 4 mL/L Ecoenzyme, 4 combination NBs N2 and Ecoenzymes, and 5 mL NBs N2 with 3 replications, making a total of 30 treatment units. The research parameters included the number of leaves, leaf length, number of roots, root length, plant height, fresh weight, and plant dry weight. The results of this study showed that the treatment of 3 mL/L Ecoenzyme showed potential in increasing the number of leaves by 4 pieces: at the same time the optimal concentration of the combination of Ecoenzyme and NBs was 2 mL/L plus 5 mL NBs N2 in increasing the number of roots by 10 pieces, and the optimal concentration of NBs was 5 mL in increasing the root length by 7.07 cm, plant height by 17.10 cm leaf. length, plant weight by 4.16 g and dry weight by 0.85 g in Phalaenopsis orchids.